(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
A mandible of Oreopithecus cf. bambolii was found in Miocene sediments of the Baccinello basin (Grosseto, Tuscany). It confirms, unequivocally, the occurrence of this peculiar primate in the V2 mammal fauna of the basin. This find allows some comments on the correlation among the Miocene sites with endemic vertebrate faunas in southern Tuscany.